The ambivalence of gay liberation male homosexual politics in 1970s West Germany - Griffiths, Craig (Studies in German history, 2021)
This text explores the different ways West Germans thought about and discussed being queer in the 1970s; a decade in the midst of the Cold War, sandwiched between the decriminalisation of homosexuality in 1969 and the HIV/AIDS crisis in the early 1980s.